Subjective Economic Well-Being of Entrepreneurs During the War in Ukraine - Artem Pugachov; Lesya Lyuta; Svitlana Yanovskaya (Вісник Харківського національного університету імені В.Н. Каразіна. Серія: Психологія)
The purpose of the work is to determine the characteristics of the subjective economic well-being of entrepreneurs during the war in Ukraine. Ukrainian entrepreneurs have been working in conditions of full-scale war for more than two years. A catastrophic situation of uncertainty hinders the conduct of business, but despite this, specialists determine an increase in economic activity. Entrepreneurs working in Ukraine (N=50), aged 23 to 55, were involved in the study. The experience of entrepreneurial activity ranged from 7 to 22 years. Areas of business activity: trade, sale and lease of real estate, agronomy, construction, freight transportation, furniture production. Questionnaires, the method of incomplete sentences (modified by us), the questionnaire of subjective economic well-being (V.A. Khashchenko) and the methods of mathematical statistics were chosen as research methods. It was determined that the subjective economic well-being of the studied entrepreneurs has a moderate level of expressiveness. At the same time, there is a noticeable tendency for men to grow in negative experiences caused by a lack of finances. And for women, a positive assessment of the current well-being of the family is characteristic. It should also be said that women entrepreneurs, compared to men, experience significantly higher economic optimism, current family well-being, and overall economic well-being. Economic optimism is higher among entrepreneurs with higher education than among those with only secondary education. Not married entrepreneurs evaluate the current well-being of their own family more positively than married ones; but no differences were found in the level of subjective economic well-being depending on the presence of children, as well as depending on objective indicators and their subjective assessment by entrepreneurs of the amount of financial profit.